Effect of different intensities of inspiratory muscle exercise on cardiac autonomic control in the post-exercise recovery in healthy adults: a controlled and randomized study - Pedro Lima Souza; Leila Dal Poggetto Moreira; Lilian Pinto da Silva; Vinicius Faria Weiss; Pedro Augusto Carvalho Mira; Patrícia Fernandes Trevizan; Mateus Camaroti Laterza; Daniel Godoy Martinez (Fisioterapia e Pesquisa)
ABSTRACT This study aimed to investigate the effect of different intensities of Inspiratory Muscle Exercise (IME) on cardiac autonomic control during the period of post-exertion recovery in healthy adults. Thus, an experimental, controlled, and randomized study was conducted with 15 men aged from 18 to 40 years, including sedentary and healthy individuals. Participants underwent four IME sessions: a sham session, followed by sessions with 30%, 40%, and 60% of maximal inspiratory pressure. Pulse intervals were recorded using digital infrared photoplethysmography to obtain heart rate (HR) values. Measurements included HR, interbeat interval, standard deviation of all normal RR intervals (SDNN), root mean square of successive differences between adjacent normal RR intervals (RMSSD), percentage of adjacent RR intervals greater than 50ms (pNN50) (time domain), total power, power of low-frequency spectral bands (LF), and power of high-frequency spectral bands (HF) (ms²), LF and HF (n.u.), and LF/HF (frequency domain). These measures were assessed simultaneously for 10 minutes at rest and during recovery period (15, 30, 45, and 60 minutes). Two-way analysis of variance was used, considering a 5% significance level. We observed that RMSSD and pNN50 showed higher values compared to baseline (Time Effect: P=0.004; P<0.01, respectively). No differences were found in HRV measures in the frequency domain (Time Effect: P>0.05). Additionally, there was no difference in the comparison between intensities for all HRV measures (Session Effect: p>0.05). We conclude that, regardless of the applied load, there is a similar increase in parasympathetic cardiac autonomic modulation indices in the post-IME recovery period in healthy adults.